Healthcare Industry Jobs: Opportunities and Challenges from a Student’s Perspective - Banerjee, Rupa; Basu, Dr. Singdha (IJRDO - Journal of Social Science and Humanities Research, 2023)
This publication explores the opportunities and challenges that students encounter in pursuing healthcare industry jobs from their distinctive perspective. The healthcare sector offers a wide range of career possibilities, encompassing clinical and non-clinical roles, which attract students seeking to contribute to the field. However, students face numerous challenges when navigating this ever-evolving landscape. On the one hand, the healthcare industry presents significant opportunities for students. Advancements in medical technology, a growing emphasis on patient-centered care, and the expanding healthcare needs of aging populations create a demand for skilled professionals. Additionally, emerging fields such as digital health and genomics offer novel prospects for students to innovate and drive positive change. On the other hand, students encounter challenges in accessing healthcare industry jobs. Fierce competition for coveted positions, complex regulatory frameworks, and the need to stay updated with evolving healthcare policies pose obstacles for students. Furthermore, the rapid integration of technology in healthcare necessitates students to acquire digital literacy and adapt to new workflows.